2021
DOI: 10.1108/pr-06-2020-0414
|View full text |Cite
|
Sign up to set email alerts
|

Linking organisational values and sustainability: the role of AMO practices

Abstract: PurposeThe aim of this study was to analyse the link between the values that govern the functioning of cooperatives and their sustainability. Furthermore, the authors propose that this relationship is mediated by AMO (ability, motivation and opportunity) practices, which generate different behaviours and attitudes in their employees, thus strengthening the message of sustainable management that the directors of this kind of companies aim to transmit.Design/methodology/approachThis article presents a theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
3
0
1
Order By: Relevance
“…In its current form, the AMO framework was proposed by Bailey (1993) and it has since been developed to examine how targeted HR practices and bundles may elevate employee performance (Appelbaum et al, 2000; Jiang et al, 2013). The CMO model has become widely adopted in management (Van Beurden et al, 2021; Rincon‐Roldan and Lopez‐Cabrales, 2021), including HRM (Salas‐Vallina et al, 2021; El‐Kassar et al, 2022) as it captures the viewpoint of both the industrial psychologists (who focus on the function of hiring and training) and social psychologists (who see motivation as necessary to ensure performance) (MacInnis and Jaworski, 1989) and can be used to explore how HR practices might activate these variables.…”
Section: Introductionmentioning
confidence: 99%
“…In its current form, the AMO framework was proposed by Bailey (1993) and it has since been developed to examine how targeted HR practices and bundles may elevate employee performance (Appelbaum et al, 2000; Jiang et al, 2013). The CMO model has become widely adopted in management (Van Beurden et al, 2021; Rincon‐Roldan and Lopez‐Cabrales, 2021), including HRM (Salas‐Vallina et al, 2021; El‐Kassar et al, 2022) as it captures the viewpoint of both the industrial psychologists (who focus on the function of hiring and training) and social psychologists (who see motivation as necessary to ensure performance) (MacInnis and Jaworski, 1989) and can be used to explore how HR practices might activate these variables.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is strongly suggested that employee creativity should be strongly encouraged. With the excellence of experience and right kind of motivation the staff of hotel or restaurant can come up with a heap of innovative ideas and suggestions for implementation of sustainability initiatives (Muisyo et al, 2021;Pham et al, 2020b;Rincon-Roldan and Lopez-Cabrales, 2022). As a result organisation these days are focusing on fostering their employees green creativity since they are the most important stakeholders in their sustainability programmes.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…As discussed earlier, AMO theory has suggested three pillars that may contribute to the sustainability domain (Rincon-Roldan & Lopez-Cabrales, 2022). HR practices must go through the AMO objectives to attract and acquire the workforce that holds the knowledge and skills (A), motivation to enable them (M), and the organizational support for engaging the employees and undertaking the changes needed (O) to get the best performance possible (Bainbridge, 2015;Ozcelik & Uyargil, 2015).…”
Section: Conceptual Model Development Processmentioning
confidence: 99%